Estimation of Abuse by Teachers in Special Needs Schools in Japan - Horiguchi, Toshihiro; Takanashi, Kenji; Sato, Shoichi; Sone, Naoki (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Children with disabilities are at high risk of being abused at school by their teachers. Based on legislation in Japan, the authors assessed the implementation of measures to prevent abuse and reasonable accommodations (arrangements) available at special needs schools in Japan. Government data has concentrated only on physical maltreatment by teachers; thus, we also collected grievances from parents to estimate the prevalence rate of abuse at special education settings. Of the 1,077 schools that were sent questionnaires, 333 completed them. Educational programmes for staff were the most common measure employed to prevent abuse. Various forms of support, including communication with internet-communication technology, were provided in relation to reasonable accommodations. After the implementation of the abuse prevention act for persons with disabilities, 14 (4.20%) schools reported grievances from parents claiming that their child had been bullied by teachers. Because Japan does not have educational inspection systems, such as the United Kingdom and the Netherlands, we assumed the incidence rate. Provided that all the grievances were related to abuse, the incidence rate was 0.02–0.05% (95% CI).